Relatively bounded and compact perturbations of nth order differential operators - Terry G. Anderson (International Journal of Mathematics and Mathematical Sciences)
A perturbation theory for nth order differential operators is developed. For certain classes of operators L, necessary and sufficient conditions are obtained for a perturbing operator B to be relatively bounded or relatively compact with respect to L. These perturbation conditions involve explicit integral averages of the coefficients of B. The proofs involve interpolation inequalities.